Modern urbanization research tools and methods classification - Nazarenko, V. (Land Management, Cadastre and Land Monitoring, 2020)
The paper introduces the classification of modern urbanization research tools and scientific research methods. Urbanization is a prominent field of multidisciplinary study that describes the population dynamics, land use changes, land cover and green areas, traffic and architectural city planning and many others. The paper deals with issues of research classification, what are the main subfield of urbanization research and which scientific methods can be used in each of them. This paper explores the main urbanization research tools, such as computational, map and information and smart city toolsets. Key component of any of the above-mentioned tools is data. We classified data by its application and research subfield that it is used at. Economics study is at the heart of any modern urban scientific work. City budget, cost of living in the city, employment data and land prices are among the most widely used fields of research in this area. The paper highlights that city growth and development, Urbanization patterns, and spatial planning and distribution are prominent subfields of urbanization economics research. The article purpose is to address the challenges any new researcher encounters is lack of extensive overview and classification of available tools. The advancement in computer science and current state of computational capabilities allow for real time system modeling and geospatial data visualization in 3D. In addition to this, article presents the urbanization scientific methodology research process. This process can serve as foundation for future scientific efforts and work in urbanization and adjacent fields. Keywords. urbanization, computer vision, neural networks, prediction, visualization, land cover, GIS, real estate, system modeling, big data.